Strategi E-Commerce Rumah Tangga Produsen Produk Olahan Pangan Lokal Di Shopee - Fatahillah, Akbar Salahudin; Nurliza, Nurliza (Jurnal Bisnis Tani, 2025)
The marketing strategies of local food-processing household industries increasingly leverage e-commerce platforms, particularly Shopee, to boost sales amidst intense market competition. By applying the 4P marketing mix theory (product, price, place, promotion) and Porter’s strategy framework, effective strategies. Results indicate that promotion has the most significant impact on increasing sales and market demand, with key indicators including free shipping programs, cashback offers, and the "choose local" campaign. Additionally, informative product descriptions, product variety, competitive pricing, and accessible distribution enhance household industry competitiveness. Optimizing promotional elements is pivotal to strengthening competitive advantage, ensuring business sustainability, and fostering growth in the digital era.